The Effects of Feeding Benzoic Acid and Essential Oils on Growth Performance, Survivability and Fecal Characteristics of Grower Pigs - M. T. Thayer; A. Langemeier; S. Scotten; J. L. Nelssen; Z. Ou; J. R. Bergstrom (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 200 pigs (DNA Line 200 × 400) with an initial body weight of 81 lb were used to determine the effects of feeding benzoic acid and an essential oil blend (Vevo- Vitall and CRINA Piglets AF, DSM Nutritional Products, Parsippany, NJ) to grower pigs. There were 10 pigs per pen and 10 pens per treatment in this 28-d grower trial. Pigs were allotted by BW and randomly assigned to 1 of 2 dietary treatments. Dietary treatments included a control diet, or the control diet with added benzoic acid (6.00 lb/ ton) paired with an essential oil blend (0.20 lb/ton). For overall growth performance (d 0 to 28), adding benzoic acid and an essential oil blend to the grower diet did not affect (P>0.05) ADG, ADFI, or F/G. Throughout the duration of this study, a trend (P = 0.06) was found for an increased loss from death and removals in pigs fed the control diet compared to pigs fed a diet containing an acidifier and essential oil blend.Lawsoniawas detected in all d 28 fecal samples collected, except for one, whereasSalmonellawas not detected in any of the fecal samples. Although there was no hemolyticEscherichia colidetected, there were other coliforms that were sporadic in occurrence. When comparing fecal samples collected on d 14, there was a tendency (P = 0.10) for pigs fed the control diet to have greater amounts ofE. colidetected than those pigs fed the diet containing benzoic acid and an essential oil blend. More research is needed to confirm the reduced death loss found for pigs fed benzoic acid and an essential oil blend compared to pigs fed a control diet.
Keywords: benzoic acid; essential oils; grower pigs